Systematic Literature Review Model PBL Untuk Penguatan Kemampuan STEM Pada Pembelajaran IPA SMP - Dhea Anggun Puspita Sari; Sri Wahyuni; Sri Rejeki Dwi Astuti; Siti Shofa Assyifa’ul Qulbi Barid (Jurnal Kajian Pendidikan IPA, 2026)
Problem-Based Learning (PBL) is an instructional model that guides students to understand concepts through solving real-world problems presented at the beginning of instruction. This study aims to examine the implementation of PBL in strengthening STEM ability in science learning at the junior high school level. Based on recent empirical evidence, this review highlights the effectiveness of PBL in improving critical thinking, problem-solving, creativity, collaboration, and scientific literacy within STEM-oriented education. The study employs a Systematic Literature Review (SLR) guided by PRISMA. Articles were identified through national and international databases and selected using clear inclusion and exclusion criteria. Studies focusing on the implementation, challenges, and outcomes of  PBL in STEM-based science learning at the junior high school level were included, while conceptual and non-empirical works were excluded. The review of 20 articles indicated that the integration of  PBL significantly contributes to the enhancement of students’ STEM skills. Four main themes emerged: the alignment of PBL with STEM ability such as inquiry, experimentation, and engineering design; the role of PBL in fostering higher-order thinking and problem-solving; the impact of PBL on collaboration and communication in STEM projects; and implementation challenges related to teacher readiness, curriculum alignment, and limited resources. Overall, the results confirm that PBL is an effective pedagogical model for supporting STEM-based science education in junior high schools. This review is limited by its database scope and time range, which may exclude relevant studies. Future research is recommended to employ longitudinal designs and cross-context comparisons. This study provides insights for teachers, curriculum developers, and policymakers to optimize PBL integration through professional development, contextual learning resources, and interdisciplinary collaboration.Keywords: problem-based learning, junior high school, science learning, STEM education, systematic literature review